2008
DOI: 10.1007/s11605-008-0559-y
|View full text |Cite
|
Sign up to set email alerts
|

Value of Bronchoscopy after EUS in the Preoperative Assessment of Patients with Esophageal Cancer at or Above the Carina

Abstract: Introduction Esophageal cancer is an aggressive disease with a strong tendency to infiltrate into surrounding structures. The aim of the present study is to determine the additional value of bronchoscopy for detecting invasion of the tracheobronchial tree after endoscopic ultrasonography (EUS) in the preoperative assessment of patients with esophageal cancer at or above the carina. Materials and Methods Between January 1997 and December 2006, 104 patients were analyzed for histologically proven esophageal canc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0
4

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(6 citation statements)
references
References 16 publications
0
2
0
4
Order By: Relevance
“…In experienced hands, EUS alone may be sufficiently accurate to exclude airway invasion, but if there is uncertainly a bronchoscopy should be performed 65. This may be supplemented with endobronchial ultrasound in combination, if appropriate, with guided aspiration for cytology of mediastinal nodes.…”
Section: Stagingmentioning
confidence: 99%
“…In experienced hands, EUS alone may be sufficiently accurate to exclude airway invasion, but if there is uncertainly a bronchoscopy should be performed 65. This may be supplemented with endobronchial ultrasound in combination, if appropriate, with guided aspiration for cytology of mediastinal nodes.…”
Section: Stagingmentioning
confidence: 99%
“…Recently, some studies showed that CT virtual bronchoscopy could replace the need of fiberoptic bronchoscopy by providing similar accuracy and less invasive approach . Other investigators suggested that endoscopic ultrasonography (EUS) could examine the airway from an opposite angle, making it more powerful than bronchoscopy in detecting airway invasion even without a mucosal break . In the current study, we highlighted the prognostic value of bronchoscopic finding in this patient group.…”
Section: Discussionmentioning
confidence: 52%
“…Die Evidenzgrundlage hierfür ist aber eher gering, da systematische Studien fehlen. Eine neuere, kleinere Studie [160] favorisiert eher den EBUS als die Bronchoskopie zur frühzeitigen Identifizierung von inkurablen Patienten beim Primär-Stanging von Tumoren auf/oberhalb der Karina-Höhe. Ältere Studien [161,162] geben demgegenüber eine Treffsicherheit der Bronchoskopie mit Biopsien/Bürstenzytologie für eine Invasion der Atemwege von bis zu 96 % an, wenn die Tumoren hoch sitzen und lokal weit fortgeschritten sind.…”
Section: Hintergrundunclassified